Primordial non-Gaussianity from the completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey II: measurements in Fourier space with optimal weights. Issue 3 (11th April 2022) - Mueller, Eva-Maria; Rezaie, Mehdi; Percival, Will J; Ross, Ashley J; Ruggeri, Rossana; Seo, Hee-Jong; Gil-Marín, Héctor; Bautista, Julian; Brownstein, Joel R; Dawson, Kyle; de la Macorra, Axel; Palanque-Delabrouille, Nathalie; et al.
ABSTRACT: We present measurements of the local primordial non-Gaussianity parameter $f_{NL}^local $ from the clustering of 343 708 quasars with redshifts 0.8 < z < 2.2 distributed over 4808 deg 2 from the final data release (DR16) of the extended Baryon Acoustic Oscillation Spectroscopic Survey (eBOSS), the largest volume spectroscopic survey up to date. Our analysis is performed in Fourier space, using the power spectrum monopole at very large scales to constrain the scale-dependent halo bias. We demonstrate the robustness of our analysis pipeline with EZ-mock catalogues that simulate the eBOSS DR16 target selection. We carefully assess the impact of systematics on our measurement, exploiting a novel neural network scheme for cleaning the DR16 sample as well as test multiple contamination removal methods. We estimate the bias due to the overcorrection of the systematic removal to be sub-dominant compared to the statistical uncertainty. We find f NL = −12 ± 21 (68 per cent confidence) for the main clustering sample including quasars with redshifts between 0.8 and 2.2, after applying redshift weighting techniques, designed for non-Gaussianity measurement from large scales structure, to optimize our analysis, which improve our results by 37 per cent.